The impact of CRA agreements on community banks - Bostic, Raphael W.; Robinson, Breck L. (Journal of Banking & Finance, 2004)
We develop three empirical models to identify the impact of Community Reinvestment Act (CRA) agreements on the mortgage lending behavior of small banking institutions during the period 1990–1997. CRA agreements are pledges banking institutions make to extend levels of credit to targeted populations and are often used by institutions to reaffirm their commitment to the goals of the CRA. We hypothesize that CRA agreements increase the level of competition for mortgage loans in the targeted area, which in turn causes a reduction in the quantity of mortgage credit to be supplied by community banks. Consistent with the quantity hypothesis, the results show that CRA agreements are associated with less mortgage lending, including lending in lower-income communities (CRA lending) and in minority communities (minority lending), by small community lenders. Evidence does not support a second hypothesis – that community banks respond to the increased competition by providing credit to riskier individuals.